2022
DOI: 10.1038/s41598-022-20365-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation of volatile organic compound levels within ambient room air and its impact upon the standardisation of breath sampling

Abstract: The interest around analysis of volatile organic compounds (VOCs) within breath has increased in the last two decades. Uncertainty remains around standardisation of sampling and whether VOCs within room air can influence breath VOC profiles. To assess the abundance of VOCs within room air in common breath sampling locations within a hospital setting and whether this influences the composition of breath. A secondary objective is to investigate diurnal variation in room air VOCs. Room air was collected using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Most ambient air contaminants were only found at concentrations lower than 3 µg m −3 in their GC-MS data set, and they concluded that it was unlikely that the detected compounds with higher intensities were originating from the room air. In contrast to most other studies, Hewitt et al assessed the influence of different clinical sampling environments on breath data and did not find a significant impact, concluding that the sampling location and varying VOC levels in room air do not affect GC-MS breath measurements [27].…”
Section: Comparison To Previous Studiesmentioning
confidence: 79%
“…Most ambient air contaminants were only found at concentrations lower than 3 µg m −3 in their GC-MS data set, and they concluded that it was unlikely that the detected compounds with higher intensities were originating from the room air. In contrast to most other studies, Hewitt et al assessed the influence of different clinical sampling environments on breath data and did not find a significant impact, concluding that the sampling location and varying VOC levels in room air do not affect GC-MS breath measurements [27].…”
Section: Comparison To Previous Studiesmentioning
confidence: 79%
“…Background correction techniques can be undertaken via the calculation of an alveolar gradient that directly compares signal strength in breath to background samples, simultaneous monitoring of inhaled and exhaled breath fractions, and using a lung washout with synthetic air to identify background VOCs (Hewitt et al, 2022 ; Maurer et al, 2014 ; Phillips, 1997 ; Schubert et al, 2005 ; Spaněl et al, 2013 ; Westhoff et al, 2022 ). A common method is collecting the ambient air in the same location where breath sampling is being performed, but this will not sample VOCs that originate from the sampling equipment.…”
Section: Breath Analysis Methodologymentioning
confidence: 99%
“… 8 Orthogonal partial least-squares discriminant analysis (OPLS-DA) and PCA were performed with SIMCA 17 (Sartorius, Malmö, Sweden). The variable importance projection (VIP) score was used to select the features with the highest discrimination potential; 9 VIP-score > 1.35 was considered relevant for group separation. Permutation testing and CV-ANOVA were used to validate the OPLS-DA model.…”
Section: Methodsmentioning
confidence: 99%